Residual stresses in a welded superalloy disc: Characterization using synchrotron diffraction and numerical process modeling - Jensen, M; Dye, D; James, K; Korsunsky, A; Roberts, S; Reed, R (2002)
The residual stress state in an electron-beam welded assembly of IN718 nickel-based superalloy has been studied both experimentally and using computer modeling. Diffraction measurements were made at the European Synchrotron Radiation Facility (ESRF), using the ID11 beamline. The assembly consisted of a 1.75-mm-thick web of rolled IN718 sheet, welded between two 14-mm-thick circular forgings. Four radial scans each of 400 measuring points were made across the web at 90-deg intervals. Diffraction patterns were recorded using a charge-coupled device (CCD) detector, which enabled the collection of information from several diffraction peaks and, thus, the determination of in-plane lattice strains; the macroscopic residual strain and stress fields were then estimated using appropriate values of the diffraction elastic constants. The experimental results were compared with the predictions from a sequentially coupled thermal-mechanical model based upon the finite-element (FE) method. The agreement between the experimental data and the results from the model is reasonable. It is shown that the residual strain/stress field is strongly influenced by the constraint imposed by the geometry of the assembly, i.e., by the inner and outer forgings, and that, as a result, the web is in a state of biaxial tension. The FE model predicts that a steady state is reached during welding and, thus, that there are systematic errors associated with the strain scanning measurements. These are considered to arise from the uncertainty associated with the positioning of the assembly and a sensitivity analysis for this effect is presented.